Microbial Quality and Assessment of Dynamism of Physiologic Factors on Selected Physicochemical Properties of Waste Water - Nworie, Martin, B.; Okonta, Christian, I.; Oyibo, Okpanachi N.; Onyedinma, Emmanuel, I.; Emeka, Oparaji H. (European Journal of Applied Sciences, 2022)
Physicochemical factors are important parameter widely used in assessing the quality/competence of surrounding ecosystem. Aquatic surrounding hold a vital point of every living system in the biosphere as compromised findings in the physicochemical properties of the aquatic system proves a point of danger to live progression. Cheap and effective way of waste treatment can be achieved easily when possible interactions and changes of responsible quality marking factors of a particular body is well understood. Waste water sample were collected from Rumuekini, Rivers state, Nigeria. Reference Sample was sited 0.5 km away from the waste water reservoir. Microbial analysis of the waste water sample in the presence of the control experiment after seven (7) days of incubation showed total viable count (TVC) of 5.4 x 103 and 4.6 x 103 CFU/ml respectively for day 0; 4.4 x 103 and 2.9 x 104 respectively for day 7. Total coliform counts of the waste water in the presence of the control experiment showed total coliform count (TCC) of: 1.3 x 102 and 8.0 x 102 CFU/ml respectively for day 0; 1.8 x 103 and 3.2 x 102 CFU/ml respectively for day 7. Physicochemical properties of waste water from a dairy industry surge tank located at Rumuekini, Portharcourt showed the following: pH (5.0), temperature (41oC), conductivity (610); water dissolved minerals such as Cl-, K+, PO3, Mg2+, Ca2+ were all determined. Initial dissolved oxygen concentration (mg/l) of the waste water was determined using a probe connected to a meter with initial value of 39.4 mg/l. Biochemical oxygen demand (BOD5) was determined after five incubation days at room temperature in separate bottles optimized at varying pH levels of 4.0-9.0 in a range of 1.0 units. BOD5 decreased with increased pH values the tested samples incubated for 5 days. pH 5.0 gave a significant reduction of the oxygen exertion (1400 mg/ml) while pH 4.0, 6.0, 7.0 showed an oxygen exertion (BOD5) of 1978, 2778, and 2965 mg/ml respectively. Samples incubated at 8.0 and 9.0 showed oxygen exertion of 2945 and 2899 mg/ml respectively. Other contents of the dairy waste water such as total organic carbon (TOC), total organic matter (TOM) contents were all determined respectively. Proceedings from this study showed the compromised statues of our aquatic environment and also in a wider look gave a great insight of effective modalities in water treatment; as increasing population of myriads industries in our country today pose great challenge to the competence of our aquatic body.